A sealing strip rubber compound, a sealing strip preparation method and application of the sealing strip in a sealing and plugging device on a lifting sliding door leaf hook
By loading amine antioxidants into the sealing strip adhesive onto a porous carrier, a slow release is achieved, solving the problem of easy aging of the sealing strip, extending the service life of the sealing strip, and reducing the maintenance cost of sliding doors.
Patent Information
- Application Number
- CN202510195336.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-11-07
- Estimated Expiration
- 2045-02-21
AI Technical Summary
The aging of the sealing strip material leads to a decline in sealing performance, increasing the maintenance cost of sliding doors.
By loading amine antioxidants onto a porous carrier, the antioxidants are slowly released, thus slowing down the aging rate of rubber. This results in the preparation of a loaded slow-release antioxidant, which is then added to the sealing strip compound to form a porous calcium carbonate shell to improve interfacial bonding and stress dispersion.
It effectively extends the service life of the sealing strip, reduces performance degradation caused by aging, and lowers the maintenance cost of sliding doors.
Smart Images

Figure CN120118437B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of sealing strips, and particularly relates to a sealing strip glue, a sealing strip preparation method and application of the sealing strip glue in a sealing and plugging device on a lifting sliding door leaf hook column. BACKGROUND
[0002] The sealing strip glue is a glue for producing sealing strips made of elastic materials such as rubber and plastic. These materials have good elasticity, flexibility and weather resistance, and can adapt to different environmental conditions such as temperature changes and ultraviolet radiation. Common sealing strip glues include ethylene-propylene-diene monomer (EPDM), polyvinyl chloride (PVC), thermoplastic styrene-butadiene rubber (TPE), silicone glue, etc.
[0003] The development history of sealing strips can be traced back to the 20th century. Early sealing strips were mostly solid strips. With the progress of science and technology, sponge-like sealing strips and composite sealing strips have gradually developed. The functions of sealing strips include waterproofing, sealing, sound insulation, dustproofing, temperature insulation, shock absorption, warmth retention, and protection against wind and rain. Sealing strips are widely used in the fields of automobiles, buildings, aerospace, etc., and are important components of automobiles, building doors and windows, household appliances, etc.
[0004] The lifting sliding door is a common sliding door with a lifting system installed. The lifting system uses the principle of leverage to control the lifting and lowering of the door leaf by rotating the handle, thereby realizing the opening and fixing of the door leaf. When the handle is turned downward, the pulley falls on the track of the lower frame through the transmission device connected to it, and drives the door leaf to be lifted upward. At this time, the door leaf is in an open state and can be freely pushed and pulled on the track. When the handle is turned upward, the pulley is separated from the lower frame track and the door leaf is lowered. The door leaf makes the sealing strip tightly press on the door frame through gravity. At this time, the door leaf is in a closed state. The sealing strip can bring good sealing effect, which is helpful for building energy saving and noise reduction.
[0005] In recent years, with the improvement of environmental protection and energy saving requirements, the technology of sealing strips has been continuously upgraded, mainly in material innovation and production process improvement. The aging of sealing strip glue will cause the sealing strip to harden and lose elasticity, resulting in a decrease in sealing performance, and the need to replace the sealing strip, which increases the maintenance cost of the sliding door. SUMMARY
[0006] The purpose of the present application is to provide a sealing strip glue and a sealing strip preparation method. By loading the amine antioxidant onto the porous carrier, slow release of the antioxidant is achieved, which can continuously play an anti-aging role for a long time, effectively delay the aging speed of rubber, prolong the service life of the sealing strip, and help the application of the sealing strip glue in a sealing and plugging device on a lifting sliding door leaf hook column.
[0007] The purpose of the present application can be achieved by the following technical solutions:
[0008] A sealing strip compound, comprising the following raw materials in parts by mass:
[0009] 60-80 parts of ethylene-propylene-diene rubber, 20-30 parts of chloroprene rubber, 20-30 parts of supported slow-release antioxidant, 2-3 parts of silane coupling agent KH550, 2-3 parts of accelerator, 0.5-2 parts of dispersant, 20-30 parts of thermoplastic styrene-butadiene rubber, 15-25 parts of white carbon black, and 1-2 parts of sulfur.
[0010] Further, the accelerator is any one of accelerator CZ, accelerator BZ, and accelerator DM.
[0011] Further, the dispersant is dispersant WB16 or dispersant WB212.
[0012] A preparation method of a sealing strip, comprising the following steps:
[0013] Step one: ethylene-propylene-diene rubber, chloroprene rubber, supported slow-release antioxidant, and silane coupling agent KH550 are added to a mixer, and mixed at 150-160°C for 5-10 min, then accelerator and dispersant are added, and mixed at 180-195°C for 10-15 min, then thermoplastic styrene-butadiene rubber, white carbon black, and sulfur are added, and mixed at 215-225°C for 5-10 min, to obtain a sealing strip compound.
[0014] Step two: the sealing strip compound is pressed into shape by a flat vulcanizing machine, and vulcanized at 270-280°C and a pressure of 22-25 MPa for 5-6 min, and naturally cooled, to obtain a sealing strip.
[0015] Further, the supported slow-release antioxidant is prepared by the following steps:
[0016] Amine antioxidant and anhydrous ethanol are added to a stirring kettle, stirred at 300-500 r / min for 5-10 min, then porous carrier powder is added to the stirring kettle, vacuumized, and continuously stirred for 1-1.5 h, filtered, the filter cake is washed with deionized water for 2-3 times, and vacuum dried, to obtain a supported slow-release antioxidant.
[0017] Further, the amount ratio of amine antioxidant, anhydrous ethanol, and porous carrier powder is 2g:250-300mL:20g.
[0018] Further, the amine antioxidant is any one of antioxidant RD, antioxidant A, and antioxidant IPPD.
[0019] Further, the porous carrier powder is prepared by the following steps:
[0020] Step 1: Tetrapod-shaped nano zinc oxide whiskers and deionized water are added to a reaction kettle, ultrasonic dispersion is carried out for 10-15 min, then ethylenediaminetetraacetic acid is added, stirring is carried out at 60-65℃ and 300-500 r / min for 20-24 h, suction filtration is carried out, the filter cake is washed with anhydrous ethanol for 2-3 times, and vacuum drying is carried out, thereby obtaining carboxylated tetrapod-shaped nano zinc oxide.
[0021] Step 2: Iron chloride hexahydrate and deionized water are added to a reaction kettle and stirred to dissolve, then carboxylated tetrapod-shaped nano zinc oxide is added and ultrasonic dispersion is carried out for 10-15 min, then ferrous sulfate heptahydrate is added, ammonia water with a mass fraction of 25% is added dropwise at 65-75℃ and 500-800 r / min, after the dropwise addition is completed, oleic acid is added and stirring reaction is continuously carried out for 60-80 min, thereby generating magnetic nano magnetite on the surface of the carboxylated tetrapod-shaped nano zinc oxide by a hydrothermal method of electrostatic self-assembly, the product is centrifugally washed with anhydrous ethanol and deionized water for 2-3 times respectively, and vacuum drying is carried out, thereby obtaining magnetic magnetite composite powder.
[0022] Step 3: The magnetic magnetite composite powder and deionized water are added to a reaction kettle, ultrasonic dispersion is carried out for 10-15 min, then ethylenediaminetetraacetic acid is added, stirring is carried out at 60-65℃ and 300-500 r / min for 20-24 h, suction filtration is carried out, the filter cake is washed with anhydrous ethanol for 2-3 times, and vacuum drying is carried out, thereby obtaining carboxylated magnetic magnetite composite powder.
[0023] Step 4: A sodium carbonate solution with a concentration of 0.1 mol / L, carboxylated magnetic magnetite composite powder and a polyacrylic acid aqueous solution with a mass concentration of 0.2-0.25% are added to a reaction kettle and stirred to mix, ultrasonic dispersion is carried out for 10-15 min, then a calcium chloride solution with a concentration of 0.1 mol / L and a sodium polystyrene sulfonate aqueous solution with a mass concentration of 0.3-0.4% are mixed and added to the reaction kettle, stirring reaction is carried out at 70-80℃ and 500-800 r / min for 1.5-2 h, thereby making the carboxylated magnetic magnetite composite powder particles coated with a porous calcium carbonate shell layer, the product is magnetically separated, the product is washed with deionized water for 2-3 times, and vacuum drying is carried out, thereby obtaining a porous carrier powder.
[0024] Further, in step 1, the amount ratio of the tetrapod-shaped nano zinc oxide whiskers, deionized water and ethylenediaminetetraacetic acid is 1 g:300-500 mL:0.3-0.5 g.
[0025] Further, in step 2, the amount ratio of the iron chloride hexahydrate, deionized water, carboxylated tetrapod-shaped nano zinc oxide, ferrous sulfate heptahydrate, ammonia water and oleic acid is 8-8.5 g:150-180 mL:2 g:4.5-5 g:18-20 mL:5 g.
[0026] Further, the ratio of the amount of use of the magnetic ferroferric oxide composite powder, deionized water and ethylenediaminetetraacetic acid in step 3 is 1g: 300-500mL: 0.3-0.5g.
[0027] Further, the ratio of the amount of use of the sodium carbonate solution, the carboxylated magnetic ferroferric oxide composite powder, the polyacrylic acid aqueous solution, the calcium chloride solution and the sodium polystyrene sulfonate aqueous solution is 20mL: 0.2-0.25g: 8-10mL: 20mL: 8-10mL.
[0028] Application of a sealing strip in a sealing and plugging device on a lifting sliding door leaf hook.
[0029] The beneficial effects of the present application are:
[0030] The sealing strip rubber material of the present application adds a supported slow-release antioxidant, which realizes slow release of the antioxidant by loading the amine antioxidant onto a porous carrier, can continuously play an anti-aging role for a long time, effectively delays the aging speed of the rubber, prolongs the service life of the sealing strip, reduces the performance decline caused by aging, such as increase of hardness and decrease of tensile strength, and application in the sealing and plugging device helps to reduce the maintenance cost of the lifting sliding door.
[0031] The porous carrier powder of the supported slow-release antioxidant is based on four-needle-shaped nano zinc oxide whiskers, the four-needle-shaped nano zinc oxide whiskers have a unique three-dimensional space structure, can provide good skeleton support, is conducive to loading more nano ferroferric oxide clusters, and improves the loading rate of the amine antioxidant through the porous structure. The magnetic ferroferric oxide composite powder has a large number of oxygen-containing functional groups after carboxylation, can form hydrogen bonds with the imino group in the amine antioxidant, improves the loading amount of the amine antioxidant, and has better slow-release effect.
[0032] The coating of the porous calcium carbonate shell not only protects the internal antioxidant and realizes the slow-release effect, but also further enhances the interface bonding force between the carrier and the rubber, and improves the stability of the antioxidant in the sealing strip rubber material. The unique space structure of the porous carrier powder can also play a role in dispersing stress in the sealing strip, reducing the generation and expansion of fatigue cracks, thereby significantly improving the fatigue resistance of the rubber sealing strip and prolonging its service life. BRIEF DESCRIPTION OF DRAWINGS
[0033] The present application will be further described below in conjunction with the drawings.
[0034] Figure 1 It is a structural schematic diagram of the sealing and plugging device of the present application. DETAILED DESCRIPTION
[0035] The technical solutions in the embodiments of the present application will be clearly and completely described in connection with the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative work fall within the protection scope of the present application.
[0036] Embodiment 1: The present embodiment provides a sealing strip, which is prepared by the following steps:
[0037] S1: 5 kg of four-needle-shaped nano zinc oxide whiskers and 1500 L of deionized water are added into a reaction kettle, ultrasonic dispersion is performed for 10 min, 1.5 kg of ethylenediaminetetraacetic acid is added, stirring is performed at 60°C and 300 r / min for 20 h, suction filtration is performed, the filter cake is washed with anhydrous ethanol for 2 times, and vacuum drying is performed to obtain carboxylated four-needle-shaped nano zinc oxide.
[0038] S2: 8 kg of iron chloride hexahydrate and 150 L of deionized water are added into a reaction kettle and stirred to dissolve, 2 kg of carboxylated four-needle-shaped nano zinc oxide is added and ultrasonic dispersion is performed for 10 min, then 4.5 kg of ferrous sulfate heptahydrate is added, 18 L of 25% ammonia water is added dropwise at 65°C and 500 r / min, after the dropwise addition is completed, 5 kg of oleic acid is added and stirring reaction is continuously performed for 60 min, magnetic nano magnetite is generated on the surface of the carboxylated four-needle-shaped nano zinc oxide by a hydrothermal method of electrostatic self-assembly, the product is centrifugally washed with anhydrous ethanol and deionized water for 2 times respectively, and vacuum drying is performed to obtain magnetic magnetite composite powder.
[0039] S3: 2 kg of magnetic magnetite composite powder and 600 L of deionized water are added into a reaction kettle, ultrasonic dispersion is performed for 10 min, 0.6 kg of ethylenediaminetetraacetic acid is added, stirring is performed at 60°C and 300 r / min for 20 h, suction filtration is performed, the filter cake is washed with anhydrous ethanol for 2 times, and vacuum drying is performed to obtain carboxylated magnetic magnetite composite powder.
[0040] S4: 80 L of 0.1 mol / L sodium carbonate solution, 0.8 kg of carboxylated magnetic magnetite composite powder and 32 L of 0.2% polyacrylic acid aqueous solution are added into a reaction kettle and stirred to mix, ultrasonic dispersion is performed for 10 min, then 80 L of 0.1 mol / L calcium chloride solution and 32 L of 0.3% polystyrene sulfonate sodium aqueous solution are mixed and added into the reaction kettle, stirring reaction is performed at 70°C and 500 r / min for 1.5 h, so that a porous calcium carbonate shell layer is coated on the surface of the carboxylated magnetic magnetite composite powder particles, the product is magnetically separated, the product is washed with deionized water for 2 times, and vacuum drying is performed to obtain a porous carrier powder.
[0041] S5: 80 g of antioxidant RD and 10 L of anhydrous ethanol were added to a stirred tank, stirred at 300 r / min for 5 min, then 800 g of porous carrier powder was added to the stirred tank, vacuumed and continued to stir for 1 h, filtered, the filter cake was washed with deionized water for 2 times, vacuum dried, to obtain a supported slow-release antioxidant.
[0042] S6: 600 g of EPDM, 200 g of CR, 200 g of the supported slow-release antioxidant and 20 g of silane coupling agent KH550 were added to a mixer, mixed at 150℃ for 5 min, then 20 g of accelerator CZ and 5 g of dispersant WB212 were added, mixed at 180℃ for 10 min, then 200 g of TPS, 150 g of white carbon black and 10 g of sulfur were added, mixed at 215℃ for 5 min, to obtain a sealant compound. The sealant compound was pressed into a sealant strip by a flat vulcanizing machine, vulcanized at 270℃ and a pressure of 22 MPa for 5 min, and naturally cooled, to obtain a sealant strip.
[0043] Example 2: A sealant strip was prepared by the following steps:
[0044] S1: 5 kg of four-needle-shaped nano zinc oxide whiskers and 2000 L of deionized water were added to a reaction kettle, ultrasonically dispersed for 12.5 min, then 2 kg of ethylenediaminetetraacetic acid was added, stirred at 62.5℃ and 400 r / min for 22 h, filtered, the filter cake was washed with anhydrous ethanol for 2.5 times (it can be understood that the actual operation is to mix the amount and method of washing 2 times and 3 times according to a certain proportion), vacuum dried, to obtain carboxylated four-needle-shaped nano zinc oxide.
[0045] S2: 8.25 kg of ferric chloride hexahydrate and 165 L of deionized water were added to a reaction kettle and stirred to dissolve, then 2 kg of carboxylated four-needle-shaped nano zinc oxide was added and ultrasonically dispersed for 12.5 min, then 4.75 kg of ferrous sulfate heptahydrate was added, 19 L of 25% ammonia water was added dropwise at 70℃ and 650 r / min, after the dropwise addition was completed, 5 kg of oleic acid was added and the stirring was continued for 70 min, and the magnetic nano magnetite was generated on the surface of the carboxylated four-needle-shaped nano zinc oxide by the electrostatic self-assembly method of hydrothermal method, the product was washed with anhydrous ethanol and deionized water for 2.5 times respectively, and vacuum dried, to obtain a magnetic magnetite composite powder.
[0046] S3: 2 kg of magnetic magnetite composite powder and 800 L of deionized water were added to a reaction kettle, ultrasonically dispersed for 12.5 min, then 0.8 kg of ethylenediaminetetraacetic acid was added, stirred at 62.5℃ and 400 r / min for 22 h, filtered, the filter cake was washed with anhydrous ethanol for 2.5 times, vacuum dried, to obtain carboxylated magnetic magnetite composite powder.
[0047] S4: 80 L of a 0.1 mol / L sodium carbonate solution, 0.9 kg of the carboxylated magnetic ferroferric oxide composite powder, and 36 L of a 0.225% by mass polyacrylic acid aqueous solution were added to a reaction kettle and stirred and mixed, and ultrasonic dispersion was performed for 12.5 min. Then, 80 L of a 0.1 mol / L calcium chloride solution and 36 L of a 0.35% by mass polystyrene sulfonic acid sodium aqueous solution were mixed and added to the reaction kettle, and stirring was performed at 75°C and 650 r / min for 1.75 h, so that a porous calcium carbonate shell layer was coated on the surface of the carboxylated magnetic ferroferric oxide composite powder particles. The product was separated by magnetic force, washed with deionized water 2.5 times, and vacuum dried to obtain a porous carrier powder.
[0048] S5: 80 g of the age resistor A and 11 L of anhydrous ethanol were added to a stirring kettle, stirring was performed at 400 r / min for 7.5 min, then 800 g of the porous carrier powder was added to the stirring kettle, vacuum was applied, and stirring was continued for 1.25 h. Filtration was performed, the filter cake was washed with deionized water 2.5 times, and vacuum drying was performed to obtain a supported slow-release age resistor.
[0049] S6: 700 g of the ethylene propylene terpolymer, 250 g of the chlorobutyl rubber, 250 g of the supported slow-release age resistor, and 25 g of the silane coupling agent KH550 were added to a mixer, and mixing was performed at 155°C for 7.5 min. Then, 25 g of the accelerator BZ and 12.5 g of the dispersant WB16 were added, and mixing was performed at 187.5°C for 12.5 min. Then, 250 g of the thermoplastic butadiene styrene rubber, 200 g of the white carbon black, and 15 g of sulfur were added, and mixing was performed at 220°C for 7.5 min to obtain a sealant compound. The sealant compound was pressed and formed using a flat press, and vulcanization was performed at 275°C and a pressure of 23.5 MPa for 5.5 min, and natural cooling was performed to obtain a sealant strip.
[0050] Example 3: A sealant strip was prepared by the following steps:
[0051] S1: 5 kg of the four-needle-shaped nano zinc oxide whisker and 2500 L of deionized water were added to a reaction kettle, ultrasonic dispersion was performed for 15 min, then 2.5 kg of ethylenediaminetetraacetic acid was added, stirring was performed at 65°C and 500 r / min for 24 h, and filtration was performed. The filter cake was washed with anhydrous ethanol 3 times, and vacuum drying was performed to obtain a carboxylated four-needle-shaped nano zinc oxide.
[0052] S2: 8.5 kg of ferric chloride hexahydrate and 180 L of deionized water were added into a reaction kettle and stirred to dissolve, then 2 kg of carboxylated four-needle-shaped nano zinc oxide was added and ultrasonically dispersed for 15 min, then 5 kg of ferrous sulfate heptahydrate was added, 20 L of 25% ammonia water was added dropwise at 75 DEG C and 800 r / min, after the dropwise addition was completed, 5 kg of oleic acid was added and the stirring reaction was continued for 80 min, and the magnetic nano four-oxide three-iron was generated on the surface of the carboxylated four-needle-shaped nano zinc oxide by the hydrothermal method of electrostatic self-assembly, the product was washed with anhydrous ethanol and deionized water for 3 times respectively by centrifugal washing, and vacuum drying was carried out to obtain a magnetic four-oxide three-iron composite powder.
[0053] S3: 2 kg of magnetic four-oxide three-iron composite powder and 1000 L of deionized water were added into a reaction kettle, ultrasonically dispersed for 15 min, then 1 kg of ethylenediaminetetraacetic acid was added, stirred at 65 DEG C and 500 r / min for 24 h, and then filtered, the filter cake was washed with anhydrous ethanol for 3 times, and vacuum drying was carried out to obtain a carboxylated magnetic four-oxide three-iron composite powder.
[0054] S4: 80 L of 0.1 mol / L sodium carbonate solution, 1 kg of carboxylated magnetic four-oxide three-iron composite powder and 40 L of 0.25% polyacrylic acid aqueous solution were added into a reaction kettle and stirred to mix, ultrasonically dispersed for 15 min, then 80 L of 0.1 mol / L calcium chloride solution and 40 L of 0.4% polystyrene sulfonic acid sodium aqueous solution were mixed and added into the reaction kettle, and stirring reaction was carried out at 80 DEG C and 800 r / min for 2 h, so that the carboxylated magnetic four-oxide three-iron composite powder particles were coated with a porous calcium carbonate shell layer, the product was magnetically separated, washed with deionized water for 3 times, and vacuum dried to obtain a porous carrier powder.
[0055] S5: 80 g of antioxidant IPPD and 12 L of anhydrous ethanol were added into a stirring kettle, stirred at 500 r / min for 10 min, then 800 g of porous carrier powder was added into the stirring kettle, vacuum was drawn and stirring was continued for 1.5 h, then filtered, the filter cake was washed with deionized water for 3 times, and vacuum drying was carried out to obtain a supported slow-release antioxidant.
[0056] S6: 800 g of ethylene propylene terpolymer, 300 g of chlorobutyl rubber, 300 g of supported slow-release antioxidant and 30 g of silane coupling agent KH550 were added into a mixing machine, mixed at 160 DEG C for 10 min, then 30 g of accelerator DM and 20 g of dispersant WB16 were added, mixed at 195 DEG C for 15 min, then 300 g of thermoplastic butadiene rubber, 250 g of white carbon black and 20 g of sulfur were added, mixed at 225 DEG C for 10 min, to obtain a sealant compound. The sealant compound was pressed into a sealant strip by using a flat plate vulcanizing machine, vulcanized at 280 DEG C and a pressure of 25 MPa for 6 min, and naturally cooled to obtain a sealant strip.
[0057] The brand of the ethylene-propylene-diene rubber in the examples is 4045M, the brand of the chloroprene rubber is CR244, and the brand of the thermoplastic styrene-butadiene rubber is D1107JSP. The other raw materials are commercially available products.
[0058] Comparative Example 1: On the basis of Example 3, the porous carrier powder in step S5 is replaced by conventional calcium carbonate powder, and the other steps remain unchanged to prepare a sealant.
[0059] Comparative Example 2: On the basis of Example 3, the porous carrier powder in step S5 is replaced by the carboxylated magnetic ferroferric oxide composite powder in step S3 without treatment in step S4, and the other steps remain unchanged to prepare a sealant.
[0060] Comparative Example 3: On the basis of Example 3, the carboxylated magnetic ferroferric oxide composite powder in step S4 is replaced by the magnetic ferroferric oxide composite powder in step S2 without treatment in step S3, and the other steps remain unchanged to prepare a sealant.
[0061] Comparative Example 4: On the basis of Example 3, the tetrapod-shaped nano zinc oxide whisker in step S1 is replaced by conventional rod-shaped nano zinc oxide, and the other steps remain unchanged to prepare a sealant.
[0062] The performance tests are carried out in accordance with GB / T 528-2009. The sealant samples are prepared in accordance with the methods in Examples 1-3 and Comparative Examples 1-4. The test contents include hardness (Shore A), tensile strength (MPa), and elongation at break (%). The fatigue resistance test is carried out in accordance with GB / T 15584-1995. Another group of samples is subjected to air aging treatment at 175°C for 168 h, and then the related performance is tested again. The related test results are the average values of three tests.
[0063] The results are shown in Table 1.
[0064] Table 1: Test results of the mechanical properties of the sealant samples
[0065]
[0066] As can be seen from Table 1, the sealant samples in Examples 1-3 have better mechanical properties, and can still maintain good mechanical properties after air aging treatment. The mechanical properties of the sealant samples in Comparative Examples 1-4 are poor before and after air aging.
[0067] In Comparative Example 1, the conventional calcium carbonate powder is used as the filler and carrier, and the loading effect of the amine antioxidant is poor, resulting in a decrease in the aging resistance of the sealant.
[0068] The load type slow release antioxidant added in Comparative Example 2 lacks calcium carbonate shell layer, and the monoparticle structure is not regular enough, the dispersibility and stability are poor, thus leading to the decrease of the mechanical properties of the sealing strip sample.
[0069] The mechanical properties of the sealing strip in Comparative Example 3 decrease because the carboxylated magnetic ferroferric oxide composite powder has a large number of oxygen-containing functional groups, which can form hydrogen bonds with the imino groups in the amine antioxidant, increase the loading amount of the amine antioxidant, and have a better slow release effect.
[0070] The mechanical properties of the sealing strip in Comparative Example 4 decrease, which may be because the spatial structure of the nano zinc oxide is changed. The tetrapod-shaped nano zinc oxide can play a skeleton role to stably load nano ferroferric oxide clusters, so that the load type slow release antioxidant has good structural strength and stability, thereby maintaining the structural integrity after the sealing strip is mixed and formed.
[0071] Application Example: Taking the sealing strip prepared in Example 3 as an example, the sealing strip has good mechanical properties and fatigue resistance, and can have long-term antioxidant effect, and can be applied to improve the sealing and plugging device on the hook column of the sliding door leaf, and reduce the maintenance cost of the sliding door.
[0072] The structure of the upper sealing and plugging device is shown in Figure 1 The upper plugging device includes a groove-shaped plugging piece 1, and the side of the groove-shaped plugging piece 1 is provided with a connecting plate 2, which can be fixed to the door leaf hook column by screws; and two sealing strips 3 are respectively fixed on the two side walls of the groove-shaped plugging piece 1.
[0073] It should be noted that in this text, terms such as "including", "containing" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements not only includes those elements, but also includes other elements not explicitly listed, or includes elements inherent to such process, method, article or device.
[0074] Although the embodiments of the present application have been shown and described, it can be understood by those skilled in the art that various changes, modifications, replacements and variations can be made to the embodiments without departing from the principles and spirits of the present application, and the scope of the present application is defined by the appended claims and their equivalents.
Claims
1. A sealant compound, characterized in that, By mass fraction, including the following raw materials: Ethylene propylene terpolymer 60-80 parts, chlorobutyl rubber 20-30 parts, supported slow-release antioxidant 20-30 parts, silane coupling agent KH550 2-3 parts, accelerator 2-3 parts, dispersant 0.5-2 parts, thermoplastic butadiene-styrene rubber 20-30 parts, white carbon black 15-25 parts and sulfur 1-2 parts; The supported slow-release antioxidant is prepared by the following steps: The amine antioxidant and anhydrous ethanol are added into a stirring kettle, stirred at 300-500 r / min for 5-10 min, then the porous carrier powder is added into the stirring kettle, vacuumized and continuously stirred for 1-1.5 h, filtered, the filter cake is washed with deionized water for 2-3 times, vacuum dried to obtain the supported slow-release antioxidant; The dosage ratio of the amine antioxidant, anhydrous ethanol and porous carrier powder is 2g:250-300mL:20g; the amine antioxidant is any one of antioxidant RD, antioxidant A and antioxidant IPPD; The porous carrier powder is prepared by the following steps: The sodium carbonate solution with a concentration of 0.1 mol / L, carboxylated magnetic ferroferric oxide composite powder and 0.2-0.25wt% polyacrylic acid aqueous solution are added into a reaction kettle and stirred and mixed, ultrasonic dispersed for 10-15 min, then the calcium chloride solution with a concentration of 0.1 mol / L and 0.3-0.4wt% polystyrene sulfonate aqueous solution are mixed and added into the reaction kettle, stirred and reacted at 70-80℃ and 500-800 r / min for 1.5-2 h, the product is separated by magnetic force, washed, vacuum dried to obtain the porous carrier powder; The carboxylated magnetic ferroferric oxide composite powder is prepared by the following steps: The magnetic ferroferric oxide composite powder and deionized water are added into a reaction kettle, ultrasonic dispersed for 10-15 min, then the ethylenediaminetetraacetic acid is added, stirred at 60-65℃ and 300-500 r / min for 20-24 h, the filter cake is washed with anhydrous ethanol for 2-3 times, vacuum dried to obtain the carboxylated magnetic ferroferric oxide composite powder; The magnetic ferroferric oxide composite powder is prepared by the following steps: The ferric chloride hexahydrate and deionized water are added into a reaction kettle and stirred and dissolved, then the carboxylated four acicular nanometer zinc oxide is added and ultrasonic dispersed for 10-15 min, the ferrous sulfate heptahydrate is added, 25wt% ammonia water is added dropwise at 65-75℃ and 500-800 r / min, after the dropwise addition is completed, the oleic acid is added and the reaction is continuously stirred for 60-80 min, the product is centrifugally washed with anhydrous ethanol and deionized water for 2-3 times, vacuum dried to obtain the magnetic ferroferric oxide composite powder; The carboxylated four acicular nanometer zinc oxide is prepared by the following steps: The four acicular nanometer zinc oxide whisker and deionized water are added into a reaction kettle, ultrasonic dispersed for 10-15 min, then the ethylenediaminetetraacetic acid is added, stirred at 60-65℃ and 300-500 r / min for 20-24 h, filtered, washed, vacuum dried to obtain the carboxylated four acicular nanometer zinc oxide.
2. A sealant compound as claimed in claim 1, wherein, The accelerator is any one of accelerator CZ, accelerator BZ and accelerator DM.
3. A sealant compound as claimed in claim 1, wherein, The dispersant is dispersant WB16 or dispersant WB212.
4. A sealant compound as defined in claim 1, wherein The sodium carbonate solution, carboxylated magnetic ferroferric oxide composite powder, polyacrylic acid aqueous solution, calcium chloride solution and sodium polystyrene sulfonate aqueous solution are used in a ratio of 20 mL: 0.2-0.25 g: 8-10 mL: 20 mL: 8-10 mL.
5. A sealant compound as defined in claim 1, wherein The magnetic ferroferric oxide composite powder, deionized water and ethylenediaminetetraacetic acid are used in a ratio of 1 g: 300-500 mL: 0.3-0.5 g.
6. A sealant compound as defined in claim 1, wherein The ferrous chloride hexahydrate, deionized water, carboxylated four acicular nano zinc oxide, ferrous sulfate heptahydrate, ammonia water and oleic acid are used in a ratio of 8-8.5 g: 150-180 mL: 2 g: 4.5-5 g: 18-20 mL: 5 g.
7. A sealant compound as defined in claim 1, wherein The four acicular nano zinc oxide whisker, deionized water and ethylenediaminetetraacetic acid are used in a ratio of 1 g: 300-500 mL: 0.3-0.5 g.
8. A method of producing a weather strip, characterized by The method comprises the following steps: The sealing strip rubber material is pressed and formed by a flat vulcanizing machine, vulcanized at 270-280 DEG C and 22-25 MPa for 5-6 min, and naturally cooled to obtain the sealing strip; The sealing strip rubber material is the sealing strip rubber material according to any one of claims 1-7.
9. The sealing strip prepared by the method according to claim 8 is applied to a sealing and plugging device on a lifting push-pull door leaf hook post.
Citation Information
Patent Citations
Organic solvent hydrothermal method for preparing cubic, flower-like or porous calcium carbonate
CN101928032A
Composite material as well as preparation method and application thereof
CN104497363A